EFFICIENT SYNTHESIS OF NOVEL TRICYCLIC BENZOXAZINE DERIVATIVES VIA RING OPENING OF EPOXIDES ALONG THE MP AND DFT STUDIES OF STRUCTURAL, SPECTROSCOPIC (IR, RAMAN, UV-VIS), THERMODYNAMIC, ORBITALS AND NLO PROPERTIES OF DESIRED TRICYCLIC BENZOXAZINE DERIVATI - Mansha, Asim; Zahoor, Ameer Fawad; ZAHID, FAISAL MAQBOOL; Asim, Sadia; FAISAL, SHAHLA (Journal of the Chilean Chemical Society, 2020)
Ring opening of 2-nitro phenyl glycidyl ether by chelated amino acid ester enolate provides access to desired novel benzoxazine derivative just over a few steps. Theoretical study on the molecular structure of 2,2,2-trifluoro-N-(1-oxo-2,3,3a,4-tetrahydro-1H-benzo[b]pyrrolo[1,2-d][1,4]ox-azin-2-yl) acetamide (S11) is presented by using second order Møller Plesset (MP2) as well as density functional theory (DFT) level calculations. The calculated vibrational frequencies were assigned into normal modes of vibration by the use of potential energy distribution (PED). The positive charge on all hydrogen atoms were obtained by charge distribution calculations using Mulliken, electrostatic and natural charge distributions. Similar electrophilic and nucleophilic regions were observed from the calculated electrostatic potential surface calculations. The time dependent density functional theory (TD-DFT) calculations were performed to obtain electronic transitions within the molecule. The frontier molecular orbital (FMO) analysis was leading to the possible charge transfer within the molecule. The natural bond orbital (NBO) analysis provided information regarding the interaction between the donor and acceptor in bond. The statistical thermodynamic functions (dipole moment, internal energy, enthalpy, Gibbs free energy, entropy, heat capacities and partition functions) were calculated at the range of temperature from 10-500 K